Pengaruh Fasilitas dan Kualitas Jasa terhadap Kepuasan di Bus Wisata di Tulungagung Jawa Timur - Nyo Hiwancobowiono; Enni Sustiyatik; Nur Laely (Jurnal Ilmiah Raflesia Akuntansi, 2026)
This study aims to analyze the influence of facilities on the satisfaction of tourist bus users in Tulungagung, the effect of service quality on the same satisfaction, as well as the combined impact of facilities and service quality on tourist bus user satisfaction in the region. The research adopts a positivist approach with a quantitative method. Data were collected through questionnaires, observations, and interviews. The analysis includes validity and reliability tests, classical assumption tests, and multiple linear regression to evaluate the effects of facilities and service quality on customer satisfaction with tourist buses. Facilities (X1) have a significant positive effect on user satisfaction, with a coefficient of 0.926 and a p-value of 0.000, indicating that improved facilities increase satisfaction. Conversely, service quality (X2) shows a significant negative effect, with a coefficient of -0.442 and a p-value of 0.000, suggesting that poor service quality reduces satisfaction. Simultaneously, facilities and service quality exert a significant influence, with an F-value of 206.044 and a p-value of 0.000, explaining 73.7% of the variation in user satisfaction.